Efektivitas Model Pembelajaran Flipped Classroom Pada Siswa Jenjang SD - Hevria, Silvi (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
This research is motivated by the characteristics of generation Z students with digital native characteristics. Generation Z is more oriented towards individual learning. This research is an experimental research. The test results prove that the flipped classroom learning model is effective in improving student learning outcomes in social studies material. Students who have high abilities in the experimental class increase their learning outcomes compared to the control class. Likewise, students who have low abilities in the experimental class have an increase in learning outcomes compared to students in the control class.Keywords : Effectiveness, learning model, Flipped Classroom